Penguatan Budaya Sekolah berbasis Habituasi Religius - Ilmi Nur Hidayah; Imas Kurniawaty; Muhamad Parhan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to examine more deeply the existence and procedural stages of religious habituation in strengthening the school culture at SDN 116 Cicaheum, as well as to determine the influence of religious habituation on reinforcing school culture to enhance students' religious character. The background of this research is based on the importance of forming students’ religious character through consistent and internalized religious practices within school life. This study employed a mixed-method approach with a sequential exploratory design. Qualitative data were collected through observation and in-depth interviews with classroom teachers, Islamic education teachers, the principal, and students. Meanwhile, quantitative data were obtained by distributing questionnaires to 30 students and analyzed using simple linear regression with the help of SPSS software. The results showed that religious habituation was implemented through various daily and weekly activities, such as communal prayers, recitation of short Qur’anic verses, Dhuha prayer, and religious mini projects. Quantitative findings revealed that religious habituation significantly influenced the strengthening of religious school culture, with a significance value of less than 0.001 and a regression coefficient of 1.645. In conclusion, religious habituation plays an essential role in shaping a religious school environment and promoting the sustainable and systematic development of students’ religious character.